Dengue fever outbreak among children in Karachi : experience at a tertiary care children hospital - Nagi, Abdul Ghaffar; Murad, Raffat; Baig, Mukhtiar (Bahria University Medical & Dental College, 2011)
Objective: To study the natural history of disease in terms of clinical presentation and outcome in hospitalized children with confirmed dengue cases. Methods: A case series study was conducted at National Institute of Child Health (NICH), Karachi from September through November 2006. Children presented with fever and presence of at least 2 clinical manifestations of suspected dengue infection according to WHO criteria were included in study. Patients were followed regarding clinical presentation, investigations, management and outcome. Results: A total of 152 children admitted with suspicion of having dengue fever were evaluated in the study. Dengue fever antibody IgM tested on all suspected patients along with CBC, PT/aPTT, Blood C/S, Serum protein and chest X- ray. Dengue fever IgM was positive in 111 patients. A significant majority of dengue patients belonged to peri urban slums. Common presenting symptom among dengue patients was fever (100%), rash (71.17%), vomiting (52.25%), hemorrhagic manifestation (36.03%) and fits (5.40%). Among 111 dengue positive cases 65 (58.58%) were Dengue Fever (DF) cases, 40 (36.03%) were Dengue Hemorrhagic Fever (DHF) and 6 (5.4%) were cases of Dengue Shock Syndrome (DSS). Three patients expired during their stay in hospital. Conclusion: A high percentage of dengue positive cases among suspected patients and a significant proportion of dengue hemorrhagic fever and dengue shock syndrome cases demands careful investigation and management.